Analisis Pembelajaran Berdiferensiasi pada Materi Stastistik di Kelas VI Sekolah Dasar - Bayu Kurniawan; Yayuk Sumarni; Siti Fatimah; Budi Murtiyasa; Sumardi Sumardi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Statistics as a subject matter for mathematics lessons is taught from elementary school. Statistics play an important role in the progress of a nation. The role of the teacher as a person who transfers knowledge to students must pay attention to the diversity of their students so that they are able to apply appropriate methods, models and strategies in the teaching and learning process. Many teachers fail to teach statistics material in class VI elementary schools. This failure was caused by teachers not paying attention to the diversity of their students. This research aims to provide an alternative solution for how differentiated learning can be used as a way to teach statistical material in class VI elementary schools. The method used in this research uses descriptive statistical analysis and qualitative descriptive analysis to provide a comprehensive picture of the learning process in class and the results obtained with differentiated learning. The results obtained from this research are that differentiated learning is able to improve student learning outcomes, especially in statistical material in elementary schools. This result can be seen from the average student score at the beginning, namely 47.95 or in the very low category, increasing to an average of 74.55 or in the medium category.